From government to governance? The role of public and public-private foundations in portuguese cultural policy - Mendes, Tiago; Vargas, Carlos (12th International Conference on Cultural Policy Research, 2022)
We argue that the Portuguese governments have been promoting a ‘governance turn’ in its national cultural policy, testing alternative models through different frameworks and promoting local self-governance. This change encompasses governance practices such as the inclusion of both public, private and third sector agents in the institutional arrangements; as well as the search for self-sustainable financing models. Our argument is emphasized through the consideration of four case studies – Portuguese cultural foundations, either public or public-private, created between 1989 and 2011 – supervised by the member of government responsible for the culture sector. These four case studies are part of a universe of 11 public cultural foundations, substantially funded by the government but build bridges with other founders. Despite having a common legal typology form, these foundations adopt substantially different governance models. Our analysis, based on a qualitative and longitudinal analysis of their statutes and associated legislation, aims to detect the reasons that explain these asymmetries; namely comparing the composition of their governing bodies. This paper is the first comparative approach to public cultural foundations in Portugal, and is innovative when it suggests that, in Portugal, successive governments have been testing different models of cultural governance by instituting, discreetly, gradually but in a sustained way, new legal modes of co-responsibility between cultural organisations that fall within distinct levels of State administration; although in some cases, as the analysis reveals, the governance models are mitigated by an excessive control of the public government over the foundations.